Modified and Optimized Glass Electrode for pH Measurements in Hydrated Ethanol Fuel - Atilio, Natalia Cambiaghi; Fertonani, Fernando Luis [UNESP]; Oliveira, Elcio Cruz de (MDPI, 2022)
One of the quality control parameters of ethanol fuel is pH, established by the Brazilian standard ABNT NBR 10891, whose scope is specific for hydrated ethanol fuel, and by the American standard ASTM D 6423, which focuses on anhydrous ethanol fuel. This study presented a modified and optimized structure using a single solvent, both for the glass electrode and the external reference electrode, to minimize the presence of the liquid junction potential for measuring the pH of hydrated ethanol fuel. The Box–Behnken design enabled us to determine the optimal condition expected for the new measurement system, which was compared with the systems proposed by the standard references and the turning range of acid–base indicators using parametric and nonparametric tests. The results revealed that the pH values obtained by the different systems are statistically different, and that only the values obtained by this proposal are suitable for the pH range found by the indicators. The optimized electrode presented an adequate response sensitivity to the Nernst equation, having an operational behavior adequate for the modified and optimized glass electrode for pH measurements in hydrated ethanol fuel.
Keywords: chemometrics; ethanol pH; hydrous ethanol fuel; metrology; modified and optimized glass electrode; pH indicators